(untitled) (ZOO-Journal, 2021)
Wetlands are taken as the transition zone between aquatic and terrestrial habitats and are essential natural territory for numerous faunae, especially for waterbirds. The habitats for waterbirds in Phewa lake are degrading due to various anthropogenic pressures and excessively spreading invasive weeds. We applied the point count method using 12 points from Phewa dam to Pame phant to collect the seasonal data of waterbirds in the Phewa wetland during Summer 2019 and Winter 2020. We compared the abundance and diversity of waterbirds between the Summer and Winter seasons. A total of 937 individuals of 43 waterbird species from 14 families were recorded from Phewa lake during the study period. The abundance of waterbirds was found higher during Winter (U = 46, p = 0.04). The Winter season was found to be more divergent than the Summer. Shannon Wiener diversity index (H’) ranged from 0.5 - 2.51 during Summer and from 0.64 - 3.18 during Winter. Distance to forest (m) was responsible for the change in the abundance of waterbirds (β = 0.26, p = 0.03). Distance to forest (m) and distance to road (m) were responsible for the change in H’ (β= 0.005, p = 0.006 and β= -0.004, p = 0.03 respectively) and Distance to forest (m) was responsible for the change in species richness (S) (β = 0.06, p = 0.01) in Phewa wetland. So planting trees and devoid road construction may increase the abundance of waterbirds in Phewa wetland.